Comunicación emotiva como espejo de las relaciones interpersonales en YouTube: Análisis cualitativo de la lengua usada por los usuarios hispanohablantes de la plataforma - Pelttari, Sanna (fi=Turun yliopisto|en=University of Turku|, 2025)
ABSTRACT This study examines the emotional communication between Spanish-speaking YouTubers and their followers, aiming to uncover what it reveals about the interaction and interpersonal relationships among these users. Furthermore, communication is analyzed in terms of underlying phenomena potentially related to the language use on these platforms, such as the attention economy, parasocial relationships, social and emotional capital, and emotional attachment. The research data were collected from the YouTube channels of the YouTubers who participated in Tubecon Madrid in 2017. The study is based on five original publications (Articles I–V). Article I examines opening and closing greetings as well as nominal forms of address. Articles II and III focus on stance-taking and its related processes, such as evaluation, positioning, and alignment. Article II explores affective narratives and self-disclosure by YouTubers, examining how they evaluate and position themselves in relation to the object (i.e., the subject of their narratives). Article III analyzes the reception of these stories in the comments section of the videos, focusing on how the audience evaluates, positions, and aligns itself in relation to the YouTubers’ positioning in their narratives. Articles IV and V, meanwhile, investigate the use of emotional language within the Influencer Marketing (IM) framework. Article IV analyzes the emotional aspects of YouTubers’ communication in videos containing promotional content, while Article V primarily examines the emotional reception of these IM-related videos in the comments sections. Based on the results of the study, it appears that there are various linguistic and discursive practices that YouTubers use to attract attention and to foster involvement with their audience and (potential) followers on their YouTube channels. This apparently contributes not only to their social capital, but also to the nature of parasocial relationships between these users. The use of emotive lexicon and multiple, albeit often repetitive, emotional expressions seem to be part of the YouTubers’ regular linguistic repertoire, as well as the lively use of non-verbal resources in their videos. These characteristics were clearly reflected in opening and closing greetings, stance-taking, self-disclosure, and promotional content. In fact, these aspects and involvement strategies were also evident in the mostly positive comments from the audience. In addition, the comments provided information on the apparent importance of YouTubers to users who leave comments. This was evident in comments within, for instance, self-disclosure, gratitude, or admiration addressed to the YouTubers. The content of comments indicating emotional attachment made up the majority of the analyzed data. The intensity and striking presence of emotive linguistic and discursive practices in my analysis could be seen as emotional capital that users accumulate through secondary socialization, personal observation, and experience. Indeed, the underlying phenomena presented in this study seem to be reflected in communication, particularly those of an emotional nature, among YouTube users—both YouTubers and their audience—whose linguistic or discursive practices strengthen the impact of these phenomena. In other words, these phenomena and language practices may reinforce one another, enhancing interaction and interpersonal relationships between YouTubers and their followers. The findings of the study suggest that the use of emotive language is predominantly influenced by the attention economy that YouTubers and commentators actively pursue. Their emotive manifestations are a key element in attracting attention. Both groups endeavor to foster parasocial relationships through various communicative acts and discursive practices that bolster involvement with their targets (YouTubers or audience), although the study unmistakably highlights the role of commentators as fans. The results indicate that the social and emotional capital of both groups of users appear to derive benefit from this asynchronous interaction. KEYWORDS: YouTube, emotional communication, videos, comments, attention economy, parasocial relationships, emotional attachment, social capital, emotional capital, communicative acts, involvement, involvement strategies

TIIVISTELMÄ Väitöstutkimukseni käsittelee espanjankielisten tubettajien ja heidän seuraajiensa välistä emotionaalista viestintää ja tavoitteena on selvittää, mitä se kertoo näiden käyttäjien keskinäisistä vuorovaikutussuhteista. Lisäksi aineistoa tarkastellaan sosiaalisen median kielenkäyttöön mahdollisesti liittyvien taustailmiöiden, kuten huomiotalouden, parasosiaalisten suhteiden, sosiaalisen ja emotionaalisen pääoman, sekä emotionaalisen kiintymyksen näkökulmasta. Tutkimusaineisto on kerätty Tubecon Madrid -tapahtumaan vuonna 2017 osallistuneiden tubettajien videoista ja niihin liittyvistä kommenteista. Tutkimus koostuu viidestä alkuperäisjulkaisusta (Artikkeli I–V). Artikkeli I tarkastelee tubettajien alku- ja lopputervehdyksiä sekä nominaalisia puhuttelumuotoja. Artikkeli II käsittelee tubettajien affektiivisia tarinoita, henkilökohtaisia paljastuksia sekä sitä, miten tubettajat arvioivat tarinoidensa aiheita ja miten he asemoivat itsensä suhteessa niihin. Artikkelissa III huomio keskittyy edellä mainittujen tarinoiden vastaanottoon ja siihen, miten yleisö arvioi ja asemoi itsensä kommenteissaan suhteessa tubettajien tarinoissa esittämään positiointiin. Artikkeli IV puolestaan analysoi tubettajien erityisesti emotionaalista kielenkäyttöä vaikuttajamarkkinointia sisältävissä videoissa ja artikkelissa V kuvataan näiden markkinointiviestintää sisältävien videoiden erityisesti emotionaalista vastaanottoa kommenttikentässä. Tutkimustulosten perusteella näyttää siltä, että tubettajat pyrkivät monin kielellisin ja diskursiivisin keinoin saamaan yleisön huomion sekä edistämään yleisön ja (mahdollisten) seuraajien sitoutumista YouTube-kanavillaan. Tämän vaikuttanee sekä käyttäjien sosiaaliseen pääomaan että heidän välisisiin (para)sosiaalisiin suhteisiinsa. Moninaiset ja paikoin voimakkaat, joskin usein samankaltaisina toistuvat tunneilmaisut vaikuttavat olevan tubettajien tavanomaista kielellistä repertuaaria unohtamatta usein ilmeikkään sanattoman viestinnän merkitystä tubettajien videoissa. Nämä kielelliset käytännöt tulivat esille videoiden tervehdyksissä ja nominaalisissa puhuttelumuodoissa, asennoitumisessa, henkilökohtaisissa paljastuksissa sekä markkinointisisällöissä. Itse asiassa nämä samat kielelliset keinot ja sitouttavat käytänteet tulivat esille myös katsojien jättämissä ja pääasiallisesti myönteisissä kommenteissa. Lisäksi kommentit tarjoavat lisätietoa myös tubettajien ilmeisestä tärkeydestä ja tämä tuli ilmeiseksi, esimerkiksi, henkilökohtaisia paljastuksia, kiitollisuutta ja ihailua kuvastavissa kommenttisisällöissä. Emotionaalisesta kiintymyksestä viestivät kommenttisisällöt ja kommunikatiiviset aktit muodostivat suurimman osan analysoidusta aineistosta. Tunteita herättävien kielellisten ja diskursiivisten käytäntöjen voimakkuuden lisäksi myös niiden silmiinpistävä läsnäolo analyysissani voidaan nähdä myös emotionaalisena pääomana, jota käyttäjät keräävät sekundäärisen sosiaalisaation, henkilökohtaisen havainnoinnin ja kokemuksen kautta. Tutkimustulosten perusteella voidaan arvioida, edellä mainitut taustailmiöt heijastuvat YouTuben käyttäjien, niin tubettajien kuin kommentoijienkin, erityisesti emotionaalisessa kielenkäytössä, joka puolestaan voi vahvistaa kyseisten ilmiöiden merkitystä. Toisin sanoen, ehkä näiden ilmiöiden ja kielenkäytön välillä on toisiaan ruokkiva ja toisistaan ammentava suhde, joka vaikuttaa tubettajien ja heidän seuraajiensa väliseen vuorovaikutussuhteeseen. Tutkimistulokset viittaavat siihen, että huomiotalous toimii käyttäjien emotionaalisen kielenkäytön tärkeimpänä vaikuttimena ja käyttäjien tunneilmaisut ovat keskeinen elementti huomion herättämisessä. Molemmat käyttäjäryhmät pyrkivät omalta osaltaan edistämään myös parasosiaalisia suhteita monilla erilaisilla ja toisten sitouttamiseen pyrkivillä kommunikatiivisilla akteilla ja kielellisillä keinoilla, joskin kommentoijien rooli tubettajia ihailevina faneina heijastuu tutkimuksen aineistossa selvästi. Tulosten perusteella voidaan lisäksi arvioida, että molemmat käyttäjäryhmien sosiaalinen ja emotionaalinen pääoma näyttäisivät hyötyvän tästä ei-synkronisesta vuorovaikutussuhteesta. ASIASANAT: YouTube, emotionaalinen viestinä, videot, kommentit, huomiotalous, parasosiaaliset suhteet, sosiaalinen pääoma, emotionaalinen pääoma, emotionaalinen kiintymys, kommunikatiiviset aktit, sitouttaminen, sitouttamisstrategiat

RESUMEN Mi investigación de tesis versa sobre la comunicación emotiva entre YouTubers hispanohablantes y sus seguidores y el objetivo es averiguar lo que revela de la interacción y las relaciones interpersonales entre estos usuarios. Además, la comunicación se observa en términos de fenómenos subyacentes que están potencialmente relacionados con el uso de la lengua de estas plataformas, como la economía de la atención, las relaciones parasociales, el capital social y emocional, y los vínculos de apego. El material se recogió de los canales de YouTube de los YouTubers que participaron en Tubecon Madrid en 2017. El estudio consta de cinco publicaciones originales (artículos I-V). El artículo I examina los saludos y las despedidas junto con las formas nominales de tratamiento. El artículo II trata de las narrativas afectivas y las autorrevelaciones de los YouTubers y de cómo estos evalúan y se posicionan en relación con el objeto, esto es, el tema de sus narraciones. El artículo III se centra en la recepción de estas historias, y en cómo la audiencia evalúa y se posiciona ante el objeto en la sección de comentarios de estos vídeos, en relación con el posicionamiento de los YouTubers en sus historias. El artículo IV analiza el lenguaje emotivo de los YouTubers en los vídeos con contenidos promocionales, en el contexto del Influencer Marketing (IM), mientras que el artículo V se enfoca en la recepción (especialmente emotiva) de los mencionados vídeos en las secciones de comentarios. A tenor de los resultados del estudio, parece que existen diversas prácticas lingüísticas y discursivas que los YouTubers utilizan para atraer la atención de su audiencia e impulsar compromiso o conectividad con ella y con los (posibles) seguidores en sus canales de YouTube. Esto aparentemente contribuye, no solo a su capital social, sino también a la naturaleza de las relaciones parasociales entre estos usuarios. El uso del léxico emotivo y las múltiples expresiones emotivas, aunque a menudo repetitivas, parecen formar parte del repertorio lingüístico habitual de los YouTubers, sin olvidar el vivaz uso de los recursos no verbales en los vídeos. Estas características se reflejaron claramente en los saludos, las despedidas, la toma de postura, las autorrevelaciones y los contenidos promocionales. De hecho, estos aspectos y las prácticas de fomentar la conectividad se pusieron de manifiesto también en los comentarios, en su mayoría positivos, de la audiencia. Además, proporcionaron información sobre la aparente importancia de los propios YouTubers para los usuarios que dejan comentarios. Esto se quedó patente, por ejemplo, en las expresiones con autorrevelaciones, gratitud y admiración dirigidas a los YouTubers en los comentarios. Los contenidos que señalaban vínculos de apego constituyeron la mayor parte del material analizado. No solo la intensidad, sino también la llamativa presencia de las prácticas lingüísticas y discursivas de índole emotiva en mi análisis podría contemplarse también como el capital emotivo que los usuarios van acumulando mediante la socialización secundaria, como resultado de observación y experiencia personal por parte de los usuarios. Efectivamente, los fenómenos subyacentes presentados en este estudio parecen reflejarse en la comunicación, sobre todo de índole emotiva, de los usuarios de YouTube, y las prácticas lingüísticas o discursivas logran hasta fortalecer el impacto de estos fenómenos. En otras palabras, tal vez estos fenómenos y prácticas se alimenten y refuercen mutuamente, influyendo así en la interacción y las relaciones interpersonales entre los YouTubers y sus seguidores. Los resultados del estudio sugieren que la economía de la atención funciona como hilo conductor de la comunicación emotiva, esto es, las manifestaciones emotivas por parte de los YouTubers y los comentaristas constituyen el elemento clave para atraer la atención. Ambos grupos buscan fomentar las relaciones parasociales, mediante diversos actos comunicativos y prácticas discursivas que impulsan cierto compromiso o conectividad con sus destinatarios (YouTubers o audiencia), aunque la función de los comentaristas como fans queda patente en el estudio. Las prácticas lingüísticas indican, además, que el capital social y emotivo de ambos grupos de usuarios se benefician de esta interacción no sincrónica. PALABRAS CLAVE: YouTube, communicación emotiva, vídeos, comentarios, economía de atención, vínculos de apego, capital social, capital emocional, actos comunicativos, compromiso, estrategias de compromiso